Facets of the polytope of legal sequences - Campêlo, Manoel (2017)
A sequence of vertices in a graph is called a (total) legal dominating sequence if every vertex in the sequence (totally) dominates at least one vertex not dominated by the ones that precedes it, and at the end all vertices of the graph are (totally) dominated. The Grundy (total) domination number of a graph is the size of the largest (total) legal dominating sequence. In this work, we present integer programming formulations for obtaining the Grundy (total) domination number of a graph, we study some aspects of the polyhedral structure of one of them and we test the performance of some new valid inequalities as cuts.